2019
DOI: 10.1016/j.jtcvs.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chlorhexidine mouthwash to reduce pneumonia after cardiac surgery: A systematic review and meta-analysis

Abstract: Objective: Postoperative pneumonia is one of the most common complications after cardiac surgery, entailing increased patient morbidity, mortality, and health care burden. The primary aim of this study was to assess whether preoperative chlorhexidine mouthwash is associated with reduced postoperative pneumonia after cardiac surgery.Methods: A comprehensive systematic search of NLM Pubmed, Embase, Scopus, and Cumulative Index of Nursing and Allied Health was executed to include the studies since inception to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Diaphragmatic atrophy is also noted with prolonged paralysis, depicted as a diaphragmatic thickness below 0.2 cm at end expiration. Other ultrasound modalities used include diaphragmatic thickening and diaphragmatic excursion fraction to assess function [63]. Management of diaphragmatic dysfunction typically requires supportive care, while addressing potential differential causes.…”
Section: Phrenic Nerve Injury and Diaphragmatic Dysfunctionmentioning
confidence: 99%
“…Diaphragmatic atrophy is also noted with prolonged paralysis, depicted as a diaphragmatic thickness below 0.2 cm at end expiration. Other ultrasound modalities used include diaphragmatic thickening and diaphragmatic excursion fraction to assess function [63]. Management of diaphragmatic dysfunction typically requires supportive care, while addressing potential differential causes.…”
Section: Phrenic Nerve Injury and Diaphragmatic Dysfunctionmentioning
confidence: 99%
“…Our prediction model may also play an important role in identifying and targeting high-risk patients for preventative measures. Several interventions have been shown to signi cantly reduce the incidence of POP, including subglottic secretion drainage [33], preoperative chlorhexidine mouthwash [34], and silvercoated endotracheal tubes [35]. Speci c interventions and appropriate preventative measures targeting high-risk patients identi ed by our prediction model may yield substantial clinical and economic bene ts.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study of hospitalized patients have also shown that pathogenic microorganisms are present in patients’ mouths from day one and show an increasing trend during hospitalization [ 35 ]. Therefore, it seems that the use of CHX in COVID-19 patients who have altered oral flora, whether in a hospital or non-hospital setting is an important procedure to improve the symptoms in these patients [ 25 , 36 ].…”
Section: Chlorhexidine (Chx)mentioning
confidence: 99%
“…A systematic review in 2016 of more than 38 RCTs found that increased oral hygiene by mouthwashes can prevent developing ventilator-associated pneumonia in critically ill patients [21]. Different studies have evaluated the antiviral effect of Povidone Iodine, 0.12%-chlorhexidine gluconate, Cetylpyridinium chloride, C31 G, chloroxylenol, benzalkonium chloride and cetrimide/Chlorhexidine [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%